Answer:
The third option
Step-by-step explanation:
The given expression is:
(x+2)² + 5(x+2) - 6 = 0
Let's check each of the given options:
1- Option A:
(u+2)² + 5(u+2) - 6 = 0
At u = x - 2, the expression would become:
(x-2+2)² + 5(x-2+2) - 6 = 0
x² + 5(x) - 6 = 0 ..........> This option is incorrect
2- Option B:
u² + 4 + 5u - 6 = 0
At u = x-2, the expression would become:
(x-2)² + 5(x-2) - 2 = 0 ..........> This option is incorrect
3- Option C:
u² + 5u - 6 = 0
At u = x+2, the expression would become:
(x+2)² + 5(x+2) - 6 = 0 .........> This option is correct
4- Option D:
u² + u - 6 = 0
At u = x+2, the expression would become:
(x+2)² + (x+2) - 6 = 0 ..........> This option is incorrect
Hope this helps :)